2003
DOI: 10.1016/s0891-5245(02)88329-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative health care practices among children

Abstract: Pediatric nurses should ask parents and children about CAM use in an open manner that promotes discussion. Further refinement of the screening tool is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 0 publications
5
50
2
2
Order By: Relevance
“…The proportion of reported complementary and alternative medicine use observed in this study was higher than has been reported for the general pediatric population, 5,7,9 and in children with neuromuscular disorders in general, 13 and muscular dystrophy in particular. 13,14 Similarly, the proportion of use in this population was higher than what has been reported for adults with neurologic disorders 18 or functional disabilities.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…The proportion of reported complementary and alternative medicine use observed in this study was higher than has been reported for the general pediatric population, 5,7,9 and in children with neuromuscular disorders in general, 13 and muscular dystrophy in particular. 13,14 Similarly, the proportion of use in this population was higher than what has been reported for adults with neurologic disorders 18 or functional disabilities.…”
Section: Discussioncontrasting
confidence: 82%
“…14 A variety of complementary and alternative therapies have been reported among pediatric populations, including chiropractic manipulation, herbal therapy, homeopathy, prayer, massage, special diets, megavitamins, acupuncture, and aquatherapy. 4,7,10,[12][13][14] Factors noted to influence use included child age 6,7,12 and disease state, 12 parent/caregiver age, 6 race, 7 and use of complementary and alternative medicine, [6][7][8][9][10]12 maternal education level, 12 healthcare provider recommendation, 10 and geographical region of residence 8,9 ; however, these findings have not been consistently replicated. A common limitation of many studies is the use of small clinic-based samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High prevalence of CAM use also is reported among children with chronic diseases (eg, functional and organic gastrointestinal diseases 3 ), those with unvaccinated or partially vaccinated status, 4 and those with life-threatening diseases (eg, cancer 5 ). Typical CAM modalities used in the pediatric population include herbs, vitamins, and homeopathic and nutritional supplements, but these modalities significantly varied by the child's age (eg, massage in infants, 6 prayer or faith healing in adolescents 7 ), country of origin, and nature of disease (eg, biofeedback and guided imagery in pediatric pain management service). [8][9][10] Several studies examined the effect of pediatric CAM use on doctor-parent and doctor-child communication.…”
mentioning
confidence: 99%